ASSESSMENT OF THE IMPACT OF HEALTH EDUCATION ON ATTITUDE, KNOWLEDGE, AND GLYCEMIC CONTROL IN PATIENTS WITH TYPE II DIABETES MELLITUS - USMAN, A; TUFAIL, N; JAMIL, MF; SHAHEEN, A; ANJUM, R; SHAMS, AF (Biological and Clinical Sciences Research Journal, 2023)
To assess the impact of education on attitude, knowledge, and practices in patients with type II DM. The case-control study was conducted in Nishtar Medical Hospital from January 2021 to January 2022. Patients aged > 40 years diagnosed with type II DM were included in the study. A total of 80 patients were included and were randomly divided into cases (n=40) and controls (n=40). The participants in the case group were educated about their disease, diets, lifestyle changes, and drugs. Patients in the control group were not provided any health education. Patients were followed up after every two months for six months. Random plasma glucose (RPG) and HbA1C were measured at baseline and follow-up visits. Knowledge and practices regarding DM were assessed using a questionnaire administered to each patient at baseline and during follow-up. Answers were recorded as Yes (score 1) or No (score 0). In the case group, RPR showed a declining trend from baseline to each follow-up visit, unlike the control group. Cases had a significantly higher mean knowledge score than controls (P=0.004). Cases had a significantly higher mean attitude score than controls (P=0.003). Cases significantly increased mean practice scores than controls (P=0.001). In the case group, there was a significantly reduction in HbA1C at the last follow-up (P=0.01). Effective health education improves attitude, lifestyle, and knowledge about DM and helps achieve glycemic control in patients with type II DM.